Analysing the Multidimensional Digital Inclusiveness Index (MDII) of Rice Crop Manager (RCM): Insights from Odisha Survey - Singaraju, Niyati; Gakhar, Shalini; Bharti, Preeti; V, Anjana; Mendoza, Jared Jorim (International Rice Research Institute, 2024)
Key insights from a survey conducted in Odisha’s Puri district to assess the digital engagement of farmers and analyze the Multidimensional Digital Inclusiveness Index (MDII) of the Rice Crop Manager (RCM) tool, a digital advisory service aimed at enhancing agricultural productivity.